STRATEGI KOMUNIKASI RADIO MENARA FM BALI DALAM MEMPERTAHANKAN PENDENGAR SETIA PROGRAM ACARA DISCOMUSIC COLLECTION (DMC) - Laksmi Swaryputri, I Gusti Agung; Ngurah Singarai Yasagita, I Wayan (Jurnal Kajian Ilmu Komunikasi, 2021)
The growth and development of radio in Denpasar is going strictly competitive, therefore the radio needs to maintain their audiences for listening to their broadcast program. The radio broadcast that prioritizes interesting programs by combining various audio elements such as songs, words, other voices, broadcasters and others. Thus, the radio needs to produce good programs which can maintain and attract the audiences. According to the preceded background, the study is focusing on the strategy of Radio Menara FM Bali in maintaining their audiences, especially the fans of Disco Music Collection (DMC) program. The method of analysis used in this study is descriptive qualitative. The research instruments used are observation techniques and interviews. Meanwhile the informants involved are The Program Director, The Music Director and The Radio Announcer or Broadcaster of Menara FM Bali. As for the result, it is found that the strategy implemented by Radio Menara FM Bali in maintaining their audiences of Disco Music Collection (DMC) program is done by building a good and close relationship to the audiences, doing some promotions about Disco Music Collection (DMC) events on social media continuously, and retaining the consistency and characteristic of the broadcaster. In conclusion, the Disco Music Collection (DMC) event at Radio Menara FM Bali has a different concept from other programs and it becomes a radio program with the highest number of interaction between the audiences and the broadcasters through social media